Antecedents and Moderation Effects of Maladaptive Coping Behaviors Among German University Students - Mülder, Lina Marie; Deci, Nicole; Werner, Antonia Maria; Reichel, Jennifer L.; Tibubos, Ana Nanette; Heller, Sebastian; Schäfer, Markus; Pfirrmann, Daniel; Edelmann, Dennis; Dietz, Pavel; Beutel, Manfred E.; Letzel, Stephan; et al. (Frontiers in Psychology, 2021)
Prolonging working hours and presenteeism have been conceptualized as self-endangering coping behaviors in employees, which are related to health impairment. Drawing upon the self-regulation of behavior model, the goal achievement process, and Warr’s vitamin model, we examined the antecedents and moderation effects regarding quantitative demands, autonomy, emotion regulation, and self-motivation competence of university students’ self-endangering coping behaviors (showing prolonging working hours and presenteeism). Results from a cross-sectional survey of 3,546 German university students indicate that quantitative demands are positively related and autonomy has a u-shape connection with self-endangering coping. Emotion regulation was shown to be a protective factor for prolonging working hours. Moreover, self-motivation moderated the relationship between quantitative demands and prolonging of working hours, but not in the assumed direction. Self-motivation showed a systematic positive relationship with prolonging of working hours, but no relationship with presenteeism. Autonomy moderated the relationship of quantitative demands with both self-endangering behaviors. We found no moderating effects for emotion regulation of quantitative demands or autonomy and self-endangering behaviors. Besides further practical implications, the results suggest that lecturers should design their courses accordingly with less time pressure and university students should be trained in the use of autonomy.